Board Political Connection and Tax Avoidance: Ownership Structure as A Moderating Variable - Ni Wayan Rustiarini; I Made Sudiartana (Jurnal Dinamika Akuntansi dan Bisnis, 2021)
This study aims to examine the relationship between political connection and tax avoidance and the role of ownership structure as a moderating variable. Corporate tax avoidance is calculated using effective tax rate (ETR). The research population is manufacturing companies listed on the Indonesian Stock Exchange from 2017 to 2019. Using purposive method this study gathered data from 119 companies or 357 company-year observations. This study revealed that political connection has a negative effect on ETR. This finding indicates that the political connections may lead to nepotism practices with aim to reduce the corporate tax burden. The managerial ownership strengthens the negative relationship between political connection and ETR. However, institutional ownership weakens the negative relationship between political connection and ETR. Contrary to these two results, public ownership cannot moderate the political connection and ETR.